2014
DOI: 10.1016/j.dcn.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

An EEG/ERP investigation of the development of empathy in early and middle childhood

Abstract: Empathic arousal is the first ontogenetic building block of empathy to appear during infancy and early childhood. As development progresses, empathic arousal becomes associated with an increasing ability to differentiate between self and other, which is a critical aspect of mature empathetic ability (Decety and Jackson, 2004). This allows for better regulation of contagious distress and understanding others mental states. In the current study, we recorded electroencephalographic event-related potentials and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
85
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 80 publications
(108 reference statements)
12
85
1
3
Order By: Relevance
“…Moreover, consistent with studies in older children, infants' early, automatic, and later controlled time-locked neural responses to the perception of social interactions of others were expected in the CMST (21,22). Infants were hypothesized to show greater amplitudes for good actions than bad actions in the Nc component, a central negativity between 300 and 500 ms poststimulus that has been previously linked to automatic resource allocation.…”
Section: Significancesupporting
confidence: 48%
See 1 more Smart Citation
“…Moreover, consistent with studies in older children, infants' early, automatic, and later controlled time-locked neural responses to the perception of social interactions of others were expected in the CMST (21,22). Infants were hypothesized to show greater amplitudes for good actions than bad actions in the Nc component, a central negativity between 300 and 500 ms poststimulus that has been previously linked to automatic resource allocation.…”
Section: Significancesupporting
confidence: 48%
“…For example, examining the spatiotemporal dynamics of the neural processing when young children view social interactions can help us to better understand the contribution of domain-general processes to early moral thought. Our current knowledge of the brain circuits involved in the development of moral cognition is based on a limited number of studies with young children using electroencephalography (21)(22)(23), functional MRI (24), and lesion studies (25). Due to the methodological constraints of most neuroimaging methods, no study has yet investigated the link between the online neural processing of the perception of prosocial and antisocial others and actual moral preferences and prosocial behaviors in infants and toddlers, as well as their link to parental values.…”
Section: Significancementioning
confidence: 99%
“…It is often viewed as the simplest form of empathy and can be observed across a multitude of species from birds to rodents and humans (Edgar, Nicol, Clark, and Paul 2012), and appears very early in ontogeny (Cheng, Chen, and Decety 2014). Often, affective sharing is synonymous with emotional contagion.…”
Section: Neurobiological Mechanisms Underlying Empathymentioning
confidence: 99%
“…These include an early automatic attentional salience (N2) and late positive potentials (LPP) associated with affective arousal and affective appraisal of the stimuli, respectively, which are detectable as of 3 years of age (Cheng et al 2014; Cheng, Hung, and Decety 2012; Sheng and Han 2012). Numerous functional magnetic resonance imaging studies (fMRI) with both children (Decety and Michalska 2010) and adults (Lamm, Decety, and Singer 2011) have reliably demonstrated that when participants watch (or even imagine) another person experiencing pain, sadness or emotional distress, brain regions involved in the first-hand physical pain are activated.…”
Section: Neurobiological Mechanisms Underlying Empathymentioning
confidence: 99%
“…In one study using electroencephalography and event-related potentials (EEG/ERPs), children aged 3-9 years were shown stimuli depicting physical injuries to people. The authors demonstrated that even children this young show both an early automatic component (N200), which reflects empathic arousal, and a late-positive potential, indexing cognitive reappraisal, with the latter showing an age-related gain [47]. One cross-sectional developmental functional MRI study tested participants ranging from 7 to 40 years of age while they watched video clips of individuals being physically injured [48].…”
Section: (B) Why Empathy Has Evolvedmentioning
confidence: 99%